Rapid interchange between two distinct forms of cyanobacterial photosystem II reaction-center protein D1 in response to photoinhibition. - Clarke, A K (1993)
We have studied photoinhibition of photosynthesis in the cyanobacterium Synechococcus sp. PCC 7942, which possesses two distinct forms of the photosystem II reaction-center protein D1 (D1:1 and D1:2). We report here that when cells adapted to a growth irradiance of 50 mumol.m-2.s-1 are exposed to an irradiance of 500 mumol.m-2.s-1, the normally predominant D1 form (D1:1) is rapidly replaced with the alternative D1:2. This interchange is not only complete within the first hour of photoinhibition but is also fully reversible once cells are returned to 50 mumol.m-2 x s-1. By using a mutant that synthesizes only D1:1, we show that the failure to replace D1:1 with D1:2 during photoinhibition results in severe loss of photosynthetic activity as well as a diminished capacity to recover after the stress period. We believe that this interchange between D1 forms may constitute an active component in a protection mechanism unique among photosynthetic organisms that enables cyanobacteria to effectively cope with and recover from photoinhibition.